2016
DOI: 10.1016/j.bbi.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

MHCI promotes developmental synapse elimination and aging-related synapse loss at the vertebrate neuromuscular junction

Abstract: Synapse elimination at the developing neuromuscular junction (NMJ) sculpts motor circuits, and synapse loss at the aging NMJ drives motor impairments that are a major cause of loss of independence in the elderly. Here we provide evidence that at the NMJ, both developmental synapse elimination and aging-related synapse loss are promoted by specific immune proteins, members of the major histocompatibility complex class I (MHCI). MHCI is expressed at the developing NMJ, and three different methods of reducing MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Since a number of manipulations in addition to expression of NRG1-III can be shown to influence the rate of synapse elimination, control of synapse elimination is clearly multifactorial. Neuronal activity, as mentioned above, is clearly important [3235]. There is evidence that NRG1 expression is itself influenced by the level of activity of neurons [36,37], suggesting a mechanism by which activity may lie upstream of NRG1-III regulation of tSCs.…”
Section: Control Of Tsc Activitiesmentioning
confidence: 99%
“…Since a number of manipulations in addition to expression of NRG1-III can be shown to influence the rate of synapse elimination, control of synapse elimination is clearly multifactorial. Neuronal activity, as mentioned above, is clearly important [3235]. There is evidence that NRG1 expression is itself influenced by the level of activity of neurons [36,37], suggesting a mechanism by which activity may lie upstream of NRG1-III regulation of tSCs.…”
Section: Control Of Tsc Activitiesmentioning
confidence: 99%
“…Motor neurons seem to be the most responsive in triggering the MHCI during normal aging ( 34 , 35 ), after insults such as the axotomy ( 36 ) or ventral horn root avulsion ( 37 ) or during chronic diseases such as experimental autoimmune encephalomyelitis in mice ( 38 ). We recently reported that spinal motor neurons of transgenic mice carrying the mutant SOD1 G93A markedly activated the expression of several molecules associated with MHCI at the onset and during the progression of the disease ( 39 41 ).…”
Section: Mhci In the Cnsmentioning
confidence: 99%
“…Interestingly, several classes of immune molecules, including C1q, the initiating protein in the classical complement cascade, and MHCI, play important roles in developmental synapse elimination [61][62][63][64] . Although synapse elimination at the NMJ occurred normally in mice deficient for pivotal protein of the complement cascade C3 61 , MHCI appeared to be involved 23 . In addition, glutamatergic transmission via N-methyl-Daspartate (NMDA) receptors seemed to be involved in the Fig.…”
Section: Mechanism Of Tnfα Presynaptic Elimination During Nmj Developmentioning
confidence: 94%
“…Recently, some retrograde factors, such as BDNF/proBDNF or Sama3A/Sama7A, expressed by postsynaptic cells are found to mediate presynaptic axonal elimination 15,[18][19][20][21][22] . In addition, class I major histocompatibility complex (MHCI) has been reported to be involved in developmental synapse elimination at the NMJ 23,24 . Nevertheless, the molecular and cellular mechanisms regulating the competitions among nerve terminals on one single muscle fiber remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%